2019
DOI: 10.3390/cancers11122014
|View full text |Cite
|
Sign up to set email alerts
|

HuR Reduces Radiation-Induced DNA Damage by Enhancing Expression of ARID1A

Abstract: Tumor suppressor ARID1A, a subunit of the chromatin remodeling complex SWI/SNF, regulates cell cycle progression, interacts with the tumor suppressor TP53, and prevents genomic instability. In addition, ARID1A has been shown to foster resistance to cancer therapy. By promoting non-homologous end joining (NHEJ), ARID1A enhances DNA repair. Consequently, ARID1A has been proposed as a promising therapeutic target to sensitize cancer cells to chemotherapy and radiation. Here, we report that ARID1A is regulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 59 publications
(82 reference statements)
3
18
0
Order By: Relevance
“…However, HuR-NP did not alter the cell cycle phases in melanocytes at 24 h and 48 h after treatment. Our results revealed that the HuR-NP treatment selectively induced a G1 phase cell-cycle arrest in melanoma cells but not in melanocytes and concurred with previous results reported for other solid tumors [ 30 , 31 , 44 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, HuR-NP did not alter the cell cycle phases in melanocytes at 24 h and 48 h after treatment. Our results revealed that the HuR-NP treatment selectively induced a G1 phase cell-cycle arrest in melanoma cells but not in melanocytes and concurred with previous results reported for other solid tumors [ 30 , 31 , 44 ].…”
Section: Resultssupporting
confidence: 93%
“…Cisplatin (CDDP; 10 µg)-treated cells were used as a positive control in the annexin V assay. The ability of HuR-NP treatment inducing apoptosis in melanoma cells but not in melanocytes is in agreement with prior reports showing HuR inhibition in tumor cells but not in normal cells results in apoptotic cell death [30,31,44].…”
Section: Genetic Knockdown Of Hur In Melanoma Cells Activated the Aposupporting
confidence: 92%
See 1 more Smart Citation
“…However, the evidence is not sufficient to prove the SAR of coumarin derivatives as HuR/ARE disruptors and the binding interface has not been confirmed. In particular, CMLD-2 showed therapeutic potentials in lung, breast, and thyroid cancer cells in vitro, with implicated mechanisms relevant to HuR-RNA disruption [143][144][145].…”
Section: Other Hur/are-rna Disruptors and Therapeutic Effectsmentioning
confidence: 99%
“…6 The biological function of ELAVL1 is implicated in gametogenesis, placental growth, 7,8 and cell survival. 9 In addition, ELAVL1 can mediate the progression of inflammation and angiogenesis. 10 Moreover, previous studies have indicated that ELAVL1 can participate in the occurrence of malignant tumours.…”
Section: Introductionmentioning
confidence: 99%